Esempi di antisemitismo culturale nel romanzo ’Il cimitero di Praga’ di Umberto Eco - Cossu, Maria Grazia (Incontri. Rivista europea di studi italiani, 2012)
Examples of Cultural Anti-Semitism in Umberto Eco’s Novel Il cimitero di Praga The article draws upon Umberto Eco’s recent novel, Il cimitero di Praga, in the consideration of the relationship between narrative fiction and the collective imagination in regards to the genesis and dispersion of The Protocols of the Elders of Zion in the second half of the nineteenth century. A dangerous and mysterious text, The Protocols evoked general clamor and persecutory backlash, as it appeared to document the existence of a Judeo-Masonic conspiracy. In the work, the author also reconstructs sources of the fictional text and traces the historical, political and editorial events surrounding it, plunging into them with a gritty and irreverent realism in a chronicle of the obsession that flowed into the madness of the Shoah. Treating the subject, which is found elsewhere in the scholar’s oeuvre, requires mention of the repertoire of prejudicial accusations against the Jews throughout history, which creates, toward the end of the book, a heated and contentious debate regarding whether such delicate and reckless statements should even be made public at all. This article questions the authorial strategy in Il cimitero di Praga, and considers the novel’s literary agenda, which can be almost interpreted as a call for vigilance against manifestations of anti-Semitism still present in today’s cultural imagination.